ANALISIS KINERJA LAPORAN KEUANGAN PADA KOPERASI DI KECAMATAN BRONDONG KABUPATEN LAMONGAN PERIODE TAHUN 2017-2020 - Rohma, Alfur; Yuli, Sri Budi Cantika; Sari, Novi Primita (Program Studi Ekonomi Pembangunan, 2022)
The purpose of this study was to determine the performance of BMT BIM's financial statements. The analytical method used is the analysis of liquidity ratios, solvency ratios, and profitability ratios. Data collection techniques in this study used interviews and observation. The results of this study indicate that BMT BIM in 2017-2020 as a whole produces values ​​that do not meet the standard ratio criteria. From the calculation of the liquidity ratio as measured by the cash ratio, it produces a bad ratio because BMT BIM cash is smaller so that when the obligation matures, it is difficult to pay debts. The current ratio produces quite good criteria because BMT BIM has assets that are quite liquid in paying its short-term obligations. The solvency ratio as measured by the total debt to total asset ratio is not good, because the total assets of BMT BIM are not able to contribute adequately to the total debt owned. While the profitability ratio as measured by ROI is not good because cooperatives are less able to use their assets productively so they are not able to produce maximum SHU. ROE produces good criteria because the capital owned by cooperatives is quite reliable in producing maximum residual business results.